IMUW-APP: An instrument for measuring the usability of web applications - Ayad Hameed Mousa; Mowafak K. Mohsen; Ali M. Alnasrawi; Intedhar Shakir Nasir (Institute of Advanced Engineering and Science, 2021)
Conventional usability measurement methods for measuring web applications are costly, sometimes time-consuming, and may require professionals. The frameworks, methods, approaches, and tools in which web applications are designed can fully support these limitations. The main issue is to speed up the evaluation process of websites in an effortless manner. To overcome this limitation, this paper proposes an instrument that can use for measuring the usability of web applications (IMUW-APP). A systematic literature review was utilized to determine the instrument dimensions and their items. The validity and reliability test were conducted via face and content validity, goodness testing, and pilot study. Cronbach's Alpha, factor loading, Kaiser-Meyer-Olkin, and Barlett's test were +calculated to ensure the validity and reliability of the proposed instrument. In the light of our analyses, the obtained findings indicate that the proposed instrument (IMUWAPP) is workable and can adapt. Besides, a case study is used to verify the proposed instrument to evaluate a university website. The collecting data have been analyzed and visualized. Ultimately, the overall findings have highlighted.